Designing and Development of 30 KV DC Rectifier Amplifier for Polling Optimization on PVDF Thin Film - Ambran Hartono; Mitra Djamal; Suparno Satira; Herman Bahar; Ramli Ramli; Dadang Dadang (Jurnal ILMU DASAR, 2014)
DC high voltage amplifier is one of the important components to support of PVDF thin films polling equipment. Hardware polling is a very important tool in the characterization of PVDF thin films to increase piezoelectric properties. The existence of the problem will be difficult to obtain a high voltage DC sources of lead in the market encouraged us to design and create high-voltage DC source. In research that has been done I've been able to design and create high-voltage amplifier 30 KV DC as a producer of high electric field. To validate the performance of this high voltage DC amplifier has created further testing and measuring the output voltage. Testing is performed to determine the precision, accuracy and stability of the output voltage of the amplifier for more than 60 minutes. From the test results and output measurements performed show that the relative error of 4.5%. Tool output stability is good enough for a span of 30 minutes. This indicates that the design and manufacture of high DC voltage gain have been successful.   Keywords: DC Amplifier, Electric field, High voltage, Polling, PVDF Film